Climate resilient technologies for sustainable production of root and tuber crops - M. Nedunchezhiyan; Kalidas Pati; V.B.S. Chauhan; K.H. Gowda; R. Arutselvan; G. Suja; G. Byju (JOURNAL OF ROOT CROPS, 2024)
Root and tuber crops are mostly grown in uplands under rainfed conditions. Uncertain weather is the major constraint in rainfed farming. Root and tuber crops are propagated vegetatively by using cut tubers/stems/vines. The cut surface loses moisture quickly and is subjected to drying and decaying. Being widely spaced long duration crops, weed menace at early stage and moisture stress at later stage affect growth and development of tubers. Cowdung cap on cassava setts improved the sprouting and establishes quickly under rainfed conditions. Storing sweet potato vine cuttings with intact leaves in bundles under shade for two days prior to planting in the main field improved sprouting and establishes quickly. Ridge height of 45 cm for sweet potato and broad bed and furrow system (20 cm height) for elephant foot yam resulted in higher yield. Mulching in yams, elephant foot yam and taro conserved soil moisture, improved sprouting and establishment, suppressed weeds and increased soil fertility apart from increased tuber yield. Growing maize as intercrop in greater yam served as livestaking and added organic matter into the soil apart from higher yield and return. Green gram intercropping in elephant foot yam increased income and improved soil fertility. Grain or vegetable crops intercropping in taro increased biological efficiency of the cropping system. Drip irrigation and fertigation in greater yam, elephant foot yam and greater yam+maize intercropping system not only produced higher yield and income but also saved water and nutrients. Thus, sustainable yield and income can be obtained by following suitable climate resilient technologies. Keywords: Cowdung slurry sett treatment, Drip irrigation, Fertigation, Intercropping, Mulching